2021
DOI: 10.3389/fpsyt.2020.594541
|View full text |Cite
|
Sign up to set email alerts
|

Stress Influences the Effect of Obsessive-Compulsive Symptoms on Emotion Regulation

Abstract: Obsessive-compulsive disorder (OCD) is associated with emotion regulation impairments, namely the frequent use of maladaptive strategies such as suppression and the decreased use of reappraisal strategies. Additionally, these patients exhibit elevated stress levels. Since stress exposure affects emotion regulation abilities, stress might influence the relationship between obsessive-compulsive symptoms and emotion regulation. In this study, we explored the effects of stress and obsessive-compulsive symptoms on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 81 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…First, we conducted Shapiro–Wilk tests to estimate the normality of measures (non-normality determined at p < 0.05). Following the previous studies ( Solas et al, 2013 ; Ferreira et al, 2021 ), correlation analysis was performed using Pearson or Spearman based on the normality of variables. Results were considered statistically significant at p < 0.05 (two-tailed).…”
Section: Methodsmentioning
confidence: 99%
“…First, we conducted Shapiro–Wilk tests to estimate the normality of measures (non-normality determined at p < 0.05). Following the previous studies ( Solas et al, 2013 ; Ferreira et al, 2021 ), correlation analysis was performed using Pearson or Spearman based on the normality of variables. Results were considered statistically significant at p < 0.05 (two-tailed).…”
Section: Methodsmentioning
confidence: 99%
“…The poor curative effect of OCD patients may be caused by the heterogeneity of OCD, and there are inevitable adverse reactions in drug treatment, and some patients have poor compliance with drug treatment. In recent years, patients with OCD who have not responded well to medication have improved their symptoms after receiving therapy based on emotion regulation, providing more options for the treatment of OCD, especially for patients who do not respond to medication [6]. It is significant and, at the same time, protects patients from the adverse effects of drug treatment and allows patients to continue treatment without a psychiatrist or therapist.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Berman et al [ 22 ] demonstrated that OCD individuals frequently struggle with emotion regulation difficulties, including an inability to accept intrusive emotions and a failure to engage in goal-directed behavior. Moreover, Ferreira et al [ 23 ] observed that individuals with OCD had difficulties utilizing more adaptive strategies, such as reappraisal. Furthermore, in a non-clinical sample, higher scores on emotion regulation strategies, such as suppression and emotional clarity, were associated with OCD symptoms [ 24 ].…”
Section: Introductionmentioning
confidence: 99%